Hand transplantation: can we balance the risks and benefits?. (March 2023) - Kay, Simon P. J.; Leonard, David A.
Asking 'can we balance the risks and benefits?' implies that a quantification of both risk and benefit in hand transplantation (here the terms hand transplant and hand transplantation refer to allotransplantation of the human hand or hand and part or all of the upper limb or limbs) is possible. Despite all we have learned in recent years about hand transplantation, much remains unknown. Even if reliable methods for quantification of risk and benefit were available, fundamental issues relating to effective communication across the gulf of lived experience between the (presumably) handed surgeon and the handless patient remain. Inherent complexities mean some consider hand transplantation an unsolved problem, but we believe the medical and technical considerations fall within the ambit of a competent multidisciplinary team, and that psychosocial and ethical challenges are open to management through robust frameworks for assessment and decision making, underpinned by an extended period of assessment and dialogue, with candid acknowledgement where uncertainty remains. This respects the patient's autonomy while addressing the need for a prolonged period of informing consent. Level of evidence: V